How do students' attitudes and mathematics teachers' self-efficacy impact students' achievement in mathematics? - Joseph Andoh Fordjour; Philemon Mgnabil Tijotob; Richmond Adu - Gyamfi; Romuald Koffi Mifetu (Journal of Advanced Sciences and Mathematics Education, 2024)
Background: Mathematics holds a critical position within educational systems worldwide due to its extensive applications. At Dadieso Senior High School in Ghana, students consistently demonstrate low performance in mathematics, necessitating an investigation into potential determinants of academic achievement.Aim: This study aims to examine the impact of students' attitudes towards mathematics and the self-efficacy of mathematics teachers on students' mathematical achievements.Method: A descriptive-correlational research design was adopted, employing quantitative methods to analyze the relationships between students' attitudes, teachers' self-efficacy, and students' academic performance. The study sampled 218 students and 7 teachers, utilizing the Attitude towards Mathematics Inventory (ATMI), the Teacher Self-Efficacy Scale (TSES), and a Mathematics Achievement Test (MAT) for data collection.Results: The analysis revealed a moderate positive correlation between students' attitudes towards mathematics and their academic performance, indicating that positive attitudes are linked to better outcomes. Furthermore, a significant, albeit smaller, positive correlation was identified between teachers' self-efficacy and student achievement, highlighting the impact of teacher confidence on student success.Conclusion: Fostering positive attitudes towards mathematics among students is essential for improving academic performance. Likewise, enhancing teachers' self-efficacy substantially influences student achievement. These factors should be the focus of interventions aimed at enhancing mathematical outcomes in educational settings.